Contribution of Character Strengths to Psychology Stress, Sleep Quality, and Subjective Health Status in a Sample of Chinese Nurses - Zhang, Shu-e; Yang, Li-bin; Zhao, Chen-xi; Shi, Yu; Wang, Hong-ni; Zhao, Xin; Wang, Xiao-he; Sun, Tao; Cao, De-pin (Frontiers in Psychology, 2021)
Objectives: The main objectives of the study were (1) to describe the current state of character strengths of nurses, and (2) to explain how they affect stress, sleep quality, and subjective health status, and (3) to reveal the mediating role of stress, for the subject matter on the association between character strengths and sleep quality, and subjective health status. Methods: A cross-sectional online survey was conducted from September to October 2020 in China. A multistage stratified sampling method was used, collecting 1,221 valid questionnaires across 100 cities in 31 provinces. Results: For the participants in this survey, the level of a three dimensions of character strengths ranging from high to low was caring (4.20 ± 0.640), self control (3.53 ± 0.763), and inquisitiveness (3.37 ± 0.787). There was difference in character strengths scores across age (F = 8.171, P＜0.01), professional categories (F = 5.545, P＜0.01), and job tenure (F = 9.470, P ＜ 0.01). The results showed that character strengths significantly affected psychological stress (β=-0.365, P < 0.01), sleep quality (β = 0.312, P < 0.01) and subjective health (β = 0.398, P < 0.01) of nurses. Moreover, psychological stress partially mediated the association between character strengths and both two types of health outcomes. Conclusion: In China, character strengths of nurses are at high levels. We found that nurses with high-level character strengths are likely to experience less psychological stress and exhibit healthy psycho-physiological responses, which contributes to positive health outcomes. Finally, our study argues that strengths-based interventions of positive psychology in hospitals should be provided to minimize threats to physical and psychological health of health professionals, which is a beneficial choice for future hospital reforms in the domain of occupational health management.